Two-Port Laparoscopic Descending Colostomy with Separated Stomas for Anorectal Malformations in Newborns - Gine, Carlos; Santiago, Saioa; Lara, Alba; Laín, Ana; Lane, Victoria Alison; Wood, Richard J.; Levitt, Marc (European Journal of Pediatric Surgery, 2016)
Introduction We describe a two-port laparoscopic technique to create a colostomy in the descending colon with separated stomas for newborns with anorectal malformations.Material and Methods Six patients with an anorectal malformation underwent this procedure in the early-neonatal period. The surgical technique was performed with two ports, which allows for an accurate inspection of the abdominal contents. The first loop of the sigmoid colon is grasped through the first port and exteriorized while the attachments to the left retroperitoneum and direction of the loop are checked with the scope introduced in the second port. The division of the colon is performed extracorporally, the colon irrigated of meconium, and the distal colon moved to the second port incision. Both stomas are then fixed to the abdominal wall.Results The time of the procedure ranged from 50 to 90 minutes. A Mullerian duplication was noted in one case. Oral intake was started during the first 12 to 24 hours. No complications were seen during or after the procedure.Conclusions This technique allows for the precise localization of the colostomy with direct visualization, provides for the inspection of the internal genitalia, eliminates the incision between the two stomas and its complications, allows for painless stoma bag changes immediately after surgery, avoids twisting of the colostomy, and permits a cosmetically pleasing incision at the colostomy closure.
Keywords: anorectal malformation; colostomy; laparoscopy